Determinan Kinerja Keuangan Perusahaan Kosmetik Yang Terdaftar di BEI Tahun 2019-2024 - Hikma Latifa; Muhammad Gowon; Riski Hernando (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine the influence of company size, sales growth, independent operating costs on financial performance as measured byreturn on asset(ROA) in cosmetic companies listed on the Indonesia Stock Exchange (IDX) in 2019-2024. This research is a quantitative research, namely data in the form of numbers. The data source in this study is secondary data, namely data that is not obtained indirectly, data obtained from annual reports obtained from the company's website or from the official website of the Indonesia Stock Exchange. The population in this study is all cosmetic companies listed on the Indonesia Stock Exchange totaling 7 companies. The sample of this study uses saturated sampling where all members of the population are used as samples and the sample in this study is 42 samples. The analysis method in this study uses multiple linear regression analysis which is processed using the programSPSS versi 26.0 for windows. The results of this study indicate that company size significantly affects financial performance (ROA), sales growth does not affect financial performance (ROA), while operational costs significantly affect financial performance (ROA).